PENINGKATAN AKTIVITAS PEMBELAJARAN IPS MENGGUNAKAN METODE INKUIRI - (F34211054), Safari; AH, Maridjo; ., Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Masalah penelitian ini adalah â€œBagaimanakah peningkatan aktivitas murid dalam pembelajaran IPS diKelasÂ  IV SDN 10 Sankinahu Bengkayang, Metode yang di gunakan yaitu metode diskriptif. Hasil penelitian menunjukan adanya peningkatanÂ  yaitu (1) aktivitas fisik murid dalam pembelajaran IPS Â menggunkan metode inkuiri mengalami peningkatan dari baseline 26,66% ke siklus 3 86,66% meningkat menjadi 60% dengan kategoriâ€Cukup tinggiâ€.(2) aktivitas mental murid dalam pembelajaran IPS Â menggunakan metode inkuiri mengalami peningkatan dari baseline 21,99% ke siklus 3 85,33% meningkat menjadi 63,34% dengan kategoriâ€Tinggiâ€. (3)aktivitas emosional murid dalam pembelajaran IPS Â menggunakan metode inkuiri mengalami peningkatan dari baseline 23,33% ke siklus 3 85,69% meningkat menjadi 62,36% dengan kategoriâ€Tinggiâ€.Hal ini menunjukan bahwa pembelajaran Â Â menggunakan metode inkuiri dapat meningkat aktivitas fisik, mental, dan emosional murid di Â SDN 10 Sangkinahu Bengkayang. Kata Kunci : PeningkatanÂ  Metode Inkuiri, Aktivitas Pembelajaran Â  Abstract : The problem of this study is " How the increased activity of students in learning social studies class IV SDN 10 Sankinahu Bengkayang The method used is descriptive method . Institutional forms of survey research , with a setting in the fourth grade at SDN 10 Sangkinahu Bengkayang , this study used a procedure III cycle . Direct observation research techniques , research tool that uses the observation sheet . The results showed an increase in : (1 ) physical activity of students in IPS use the inquiry method of learning has increased from a baseline of 26.66 % to 86.66 % 3 cycles increased to 60 % in the category of " High Enough " . ( 2 ) the mental activity of students in the IPS using the inquiry method of learning has increased from a baseline of 21.99 % to 85.33 % 3 cycles increased to 63.34 % in the category of " High " . ( 3 ) the emotional activity of students in social studies learning using inquiry method increased from baseline 23.33 % to 85.69 % 3 cycles increased to 62.36 % in the category of " High ." This shows that the learning using the inquiry method can increase the activity of physical , mental , and emotional students at SDN 10 Sangkinahu Bengkayang. Key words : Improved Methods of Inquiry , Learning Activities